The Contribution of Women in Household Decision-Making (Case Study of Women Selling Spent Hens in Pagar Alam City, South Sumatra Province) - Lusi Oktapiani; M. Zulkarnain Yuliarso; Arianti, Nyayu Neti (Jurnal AGRISEP, 2026)
This study aimed to analyze the role of women selling spent hens in household decision-making in Pagar Alam City, South Sumatra Province.  This study shows the role of women who work to earn a living in household decision-making in the areas of production, household expenses, the formation of family rules, and social activities. This is important for understanding how gender equality is implemented in households.  The population of this study was women selling spent hens who also had the status of wives in the household. The research population comprised 39 individuals selected by census as respondents.  The data for this case study were collected through in-depth interviews with respondents. The obtained data were analyzed descriptively and quantitatively. Women selling spent hens in Pagar Alam City, South Sumatra Province, play a significant role in household decision-making. These women contribute an average of 47% of household income, a contribution nearly equal to their husbands' contribution to household income.  Therefore, they also play a role in household decision-making.  Decision-making by the wife herself dominates in three fields: household production (64 %), household expenditure (49 %), and forming household rules (25 %).   Decision-making by the husband and wife together, by the husband and wife, but the husband is dominant, and by the husband himself is less.